Factors influencing youth unemployment / Ahmad Shahmi Ahmad Shukri - Ahmad Shukri, Ahmad Shahmi (2022)
The number of persons employed is often related to a country's economic growth rate. Youth unemployment rate is heavily influenced by activity in the economy. When economic activity is low, there will be less production, which means businesses lay off younger workers and the number of youth unemployment rises. As a result, the youth unemployment rate in Italy will be influenced by a few factors. The purpose of this research is to find out what factors have an impact on Italy's youth unemployment rates, as well as to investigate how independent variables influence the dependent variable. The research is performed using secondary data from an economic indicator which are gross domestic product, inflation, foreign direct investment (FDI), and interest rate. The research sample consisted of time-series data on Italy's youth unemployment rate from 1991 until 2020. The result of this research showed that all the independent variables which are gross domestic product, inflation, foreign direct investment (F DI), and interest rate have a correlation with the youth unemployment rate. Using the economic indicators presented in this research, the government's policy to analyze the youth unemployment rate would benefit from this research.